Congenital Anomaly Caused by Cytomegalovirus and Toxoplasma Infections - Sunartini Noormanto (Indonesian Pediatric Society, 1996)
We report a case of a five-year-old child with congenital anomaly caused by maternal cytomegalovirus infection and toxoplasmosis, hospitalized in pediatric ward Sardjito General Hospital. The diagnosis was established from the history of illness, physical examination, and laboratory findings. The presence of microcephaly, failure to thrive, deaf and mute, congenitally transmitted infection was suspected.